Crystal Structure of Photosystem I Monomer From Synechocystis PCC 6803 - Netzer-El, Sigal Yoli; Caspy, Ido; Nelson, Nathan (Frontiers in Plant Science, 2019)
A single histidine addition to the C-terminus of PsaL of Synechocystis sp. PCC 6803 was previously reported by or lab to shift the trimer-to-monomer ratio of PSI in favor of the monomeric form. P700 re-reduction and NADP+ photo-reduction measurements of PsaLHIS strain show no effect on PSI activity in comparison to the WT trimeric PSI. Crystal structure of the monomeric PSI reveals several alterations that occurred in the trimerisation site of PSI, primarily a deformation of the C-terminus of PsaL and loss of chlorophyll a and β-carotene molecules.